Pengembangan Instrumen Penilaian Keterampilan Mengajar untuk Calon Instruktur di PT. Kita Borneo Kompeten - Satria Gantara, Muhammad Dharma; Siregar, Eveline; Mulyadi (Jurnal Pembelajaran Inovatif, 2025)
This study aims to develop an assessment instrument for instructor candidates at PT Kita Borneo Kompeten. This development uses the Chicago Public Schools (CPS) instrument development model. This development model consists of several stages, including determining the dimensions to be assessed, collecting several dimensions that have been determined, formulating the dimensions to be assessed. Furthermore, defining each aspect, determining the scale of the dimensions to be assessed. Furthermore, conducting an assessment with the rubric that has been developed, testing, socialization. The results of this development have gone through the expert judgment stage involving evaluation experts and material experts. The results of expert review to 2 experts obtained input which was then improved by the developer. The next step is a one to one trial involving learning and operations staff at PT Kita Borneo Kompeten. The results of the one to one trial stated that the instrument could be a measuring tool to assess and collect data on the teaching skills of prospective instructors at PT. Kita Borneo Kompeten.